2012
DOI: 10.1016/j.exphem.2012.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo fucosylation improves human cord blood engraftment in NOD-SCID IL-2Rγnull mice

Abstract: Delayed engraftment remains a major hurdle following cord blood (CB) transplantation. It may be due, at least in part, to low fucosylation of cell surface molecules important for homing to the BM microenvironment. Since fucosylation of specific cell surface ligands is required before effective interaction with selectins expressed by the BM microvasculature can occur, a simple 30 minute ex vivo incubation of CB HPC with fucosyltransferase (FT) - VI and its substrate (GDP-fucose) was performed to increase levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
63
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 43 publications
3
63
0
Order By: Relevance
“…A rapid decline in NK cell function occurs when IL-2 is removed from medium. 41 In vivo dependence on IL-2 for persistence is greater with ex vivo expanded cells than fresh, activated cells. 131 In vivo use of IL-2 (which can expand NK cell numbers) can lead to severe toxicity and also to Treg expansion which limits NK cell activation.…”
Section: Lymphoyte Contamination Of the Graft T-cell Contaminationmentioning
confidence: 99%
See 1 more Smart Citation
“…A rapid decline in NK cell function occurs when IL-2 is removed from medium. 41 In vivo dependence on IL-2 for persistence is greater with ex vivo expanded cells than fresh, activated cells. 131 In vivo use of IL-2 (which can expand NK cell numbers) can lead to severe toxicity and also to Treg expansion which limits NK cell activation.…”
Section: Lymphoyte Contamination Of the Graft T-cell Contaminationmentioning
confidence: 99%
“…Levels of fucosylation can be increased by incubation with α1-3 fucosyltransferase (FT)-VI. 38,40,42 Robinson et al 41 showed that fucosylation of CB HPCs can be increased from a baseline of~15% to 495% with a 30-min incubation with FT-VI at room temperature and that only the fucosylated fraction of CD34 + HPCs contributes to engraftment in NOD scid gamma mice. In addition, appearance of human CD45 + cells in the peripheral blood of NOD scid gamma mice was more rapid in mice receiving fucosylated grafts than those receiving untreated grafts and both myeloid and B-lymphoid engraftment in marrow and spleen were threefold greater than in recipients of unfucosylated grafts.…”
mentioning
confidence: 99%
“…Robinson and colleagues [70] have tried a simple 30-minute ex vivo incubation of UCB hemotopoietic progenitor cells with fucosyltransferase-VI (a1-3 fucosyltransferase) and its substrate (Guanosine diphosphate -fucose/ GDP) to increase levels of fucosylation. In their study they observed a concomitant improvement in engraftment with increased number of fucosylated CD34 cells in a NSG mouse model.…”
Section: Fucosylationmentioning
confidence: 99%
“…Such approaches have assessed fucosylation [36], pretreatment of cells with a modifi ed prostaglandin (PG) E2 [37 -39], or pretreatment of cells with an inhibitor of the enzyme dipeptidylpeptidase (DPP) 4 [40,41,51]. Fucosylation of CB cells has enhanced the homing and engrafting capability of these treated cells in sublethally irradiated NS2 mice [36].…”
Section: Enhancing Homing and Hct Engrafting Capabilities Of Cb / Hscsmentioning
confidence: 99%
“…Such approaches have assessed fucosylation [36], pretreatment of cells with a modifi ed prostaglandin (PG) E2 [37 -39], or pretreatment of cells with an inhibitor of the enzyme dipeptidylpeptidase (DPP) 4 [40,41,51]. Fucosylation of CB cells has enhanced the homing and engrafting capability of these treated cells in sublethally irradiated NS2 mice [36]. Pretreatment of mouse BM or human CB cells for minutes with a modifi ed PGE2 molecule has, respectively, enhanced the engraftment of these cells into lethally irradiated congenic mice and sublethally irradiated immune -defi cient mice [37,38], with efforts in nonhuman primates [39] and humans [52] showing safety, with a modest decrease to the time to engraftment seen in a human study in context of a double -CB transplant including one manipulated and one unmanipulated CB unit [52].…”
Section: Enhancing Homing and Hct Engrafting Capabilities Of Cb / Hscsmentioning
confidence: 99%